The Mentor’s Role Within the Company - Małgorzata Baran (Studia i Materiały)
Mentoring is an approach to business management which facilitates the utilization of human resources in the enterprise efficiently. Mentoring can be found in all shapes and sizes – ranging from formalized structures to loosely formed relationships – resulting in the retention of the most valuable employees within the firm, and providing the transfer of knowledge, skills and experience among employees. The mentoring process achieved results mainly by appointing competent, well-selected mentors. The aim of this paper is to present the role of the mentor in the enterprise. The results of a good mentor competence study are discussed and an analysis of mentor competencies – with particular emphasis on the age, gender and professional experience (measured by years of employment) – are presented. The author attempts to ascertain which competencies make the mentor fulfill his or her role in the company well. The article consists of an introduction, a brief literature review, a presentation of research results and conclusions. The conclusions of the presented analysis provide a basis for further research and the development of practical recommendations for HR managers.